A mechanism for the enhanced attachment and proliferation of fibroblasts on anodized 316L stainless steel with nano‐pit arrays. Issue 6 (8th March 2014) - Ni, Siyu; Sun, Linlin; Ercan, Batur; Liu, Luting; Ziemer, Katherine; Webster, Thomas J.
Abstract In this study, 316L stainless steel with tunable nanometer pit sizes (0, 25, 50, and 60 nm) were fabricated by an anodization procedure in an ethylene glycol electrolyte solution containing 5 vol % perchloric acid. The surface morphology and elemental composition of the 316L stainless steel were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and X‐ray photoelectron spectroscopy (XPS). The nano‐pit arrays on all of the 316L stainless steel samples were in a regular arrangement. The surface properties of the 316L stainless steel nano‐pit surface showed improved wettability properties as compared with the untreated 316L stainless steel, as demonstrated by the lower contact angles which dropped from 83.0° to 28.6 to 45.4°. The anodized 316L stainless steel surfaces with 50 nm and 60 nm diameter pits were also more rough at the nanoscale. According to MTT assays, compared with unanodized (that is, nano‐smooth) surfaces, the 50 and 60 nm diameter nano‐pit surfaces dramatically enhanced initial human dermal fibroblast attachment and growth for up to 3 days in culture. Mechanistically, this study also provided the first evidence of greater select protein adsorption (specifically, vitronectin and fibronectin which have been shown to enhance fibroblast adhesion) on the anodized 316L stainless steel compared with unanodized stainless steel. Such nano‐pit surfaces can be designed to support fibroblast growth and, thus, improve the use of 316L stainless steel for various implant applications (such as for enhanced skin healing for amputee devices and for percutaneous implants). © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1297–1303, 2014.